From crop left-overs to nutrient resource: growth-stimulating potential of biochar in nutrient solutions for wheat soilless cultivation systems - Kunnen, Kris; Ali, Md Muntasir; Lataf, Amine; Van Hees, May; Nauts, Robin; Horemans, Nele; Vandamme, Dries; Cuypers, Ann (Frontiers in Plant Science, 2024)
To reach the estimated food demands for 2050 in decreasingly suiting climates, current agricultural techniques have to be complemented by sustainably intensified practices. Focusing on circular bioeconomy, cCThe current study repurposed wheat crop residues into biochar, and investigated its potential in different plant cultivation systems, including a hydroponic cultivation of wheat (Triticum aestivum cv. Servus). Biochars resulting from varying pyrolysis parameters including feedstock composition (straw and chaff) and temperature (450 °C and 600 °C), were tested using a fast plant screening method. Biochar WBC450, produced from a combination of chaff and straw at 450 °C, was selected for further plant experiments, and used in a static leaching experiment in the Arabidopsis thaliana cultivation medium. Increased pH and EC were observed, together with an increase of most macronutrient (K, Mg, P, S) and a decrease of most micronutrient (Fe, Mn, Zn) concentrations.Considering plant growth, application of biochar resulted in concentration-dependent effects in both tested plant species (A. thaliana and wheat). It improved the vegetative yield across all tested cultivation systems. Increases in K and S, and concentration-dependent decreases in Fe and Na content in wheatgrass were observed. Biochar influenced the reproduction of hydroponically cultivated wheat by increasing the number of spikes and the number of seeds per spike. The antioxidative capacity of wheat grass, and the seed sugar and starch contents remained unaffected by biochar application. This study contributes to innovation in soilless cultivation approaches of staple crops, within the framework of closing waste loops for a circular bioeconomy.